Paediatric rheumatology in Nigeria: history, challenges and the future - Faleye, Ayodele (Frontiers in Pediatrics, 2024)
Pediatric rheumatology is a relatively new subspecialty in Nigeria. For many years, rheumatic disease had not been well-recognized or studied in Nigeria, so there has been a low suspicion index. The clinical presentation of most pediatric rheumatic diseases (PRDs) mimics nonrheumatic diseases making it a diagnostic challenge most of the time.The story has changed in Lagos since the creation of a pediatric rheumatology unit at the Lagos State University Teaching Hospital. There is now a high index of suspicion for these diseases in the hospital but no one knows about what is happening in the other 35 states of the country who do not have a pediatric rheumatologist.Major challenges being faced presently are poor awareness among healthcare workers and the community, high cost of investigations and medications, lack of pediatric rheumatologists in most hospitals in the country, lack of pediatric rheumatology training centers for both undergraduate and postgraduate training, and lack of research data. The healthcare community in Nigeria is looking forward to a future where pediatric rheumatology will be highly recognized and established.